Gender Roles in Medical Education from the Perspective of Medical Faculty Students and Their Effects on Specialty Selection - Recep Türker Bulut; Ayşe Göksu Bozdoğan; Seher Karahan; Ezgi Ağadayı (Journal of Medical Education and Family Medicine)
Objective: The purpose of this study is to ascertain the attitudes of students at a medical faculty regarding gender roles and how these attitudes affect the branch they wish to choose.Methods: This is a descriptive study. A survey form consisting of 37 questions, including the Gender Role Attitudes Scale, was delivered to students online. In statistical analyses, normality analysis was performed with the Shapiro-Wilk test. Chi-square, Student-T and ANOVA tests were applied.Results: Four Hundred Fifteen students participated in the research. A significant difference was detected between gender and the branch in which they planned to specialize (P<.001). Comfortable working conditions were more common among female students' reasons for choosing their planned specialization than male students (P=.022). Gender roles scale score of female students (60.8±9.1) was found to be higher than male students (51.3±10.2) (P<.001). The gender roles scale score did not change depending on the grades the students attended (P=.771).Conclusion: It is noteworthy that medical education has no effect on students' attitudes towards gender. Their views on the subject are shaped by the demographic characteristics of the family. It is recommended that the hidden curriculum for medical education be evaluated and developed in future studies.